Understanding Indian society: The non-brahmanic persperctive - Dahiwale, S. M. (New Delhi Rawat Publications, 2005)
Sociologists and social anthropologists have developed Indological, structural-functional and Marxian approaches towards the understanding of Indian society. Despite a distinctive history of conflict from the times of Buddha to the contemporary Ambedkar, social scientists have made non-Brahman traditions a part of broader Hinduism. In British India, although a number of social reformers had launched anti-systemic movements to challenge the hegemony of upper-caste Hindus but there are several issues of identity, power, conversion, gender inequality and social justice which have not been addressed properly.